Design And Construction Of A Dodol Dough Mixing Machine With An Electric Motor Drive With A Capacity Of 10 Kg - Kahfi, Syahri Ashabul; Siswadi, Siswadi; Riyadi, Slamet; Nugroho, Wahyu; Nugroho, Alfi; Muchid, Mochamad (Journal of System Engineering and Technological Innovation, 2024)
The process of cooking dodol dough requires the energy of several people to stir continuously until the dough produces air bubbles. Making dodol generally takes time depending on how much dough you want to cook. If we cook 10 kg of dodol dough, the time needed to cook it is approximately 10-12 hours with medium or normal heat. Currently, the household-scale dodol industry still uses manual methods for the dodol mixing process, which will require more than one person to stir for a long time, so it will take time for one repetitive job and production costs will be higher. This activity aims to create appropriate technology in the form of a dodol mixer machine. With this dodol mixer machine, it is expected to be able to produce optimal dodol dough and can increase production capacity. The method used in this activity is the selection and calculation of the components of the designed tool, the creation of a dodol mixer machine design, and continued with a demonstration of the performance of the dodol mixer machine. The result of this activity is the design of a dodol mixer machine. With a 1/2 Hp motor power, this dodol mixer machine can produce 10 kg/hour with multifunction.